Unjuk Kerja Mesin Pemanen Padi (Oryza sativa) Kombinasi Mini (Mini Combine Harvester) - Mochamad Zakky; Joko Pitoyo; Adi Prayoga (The University of Lampung, 2021)
Mini combine harvester is a modern machine used for cutting rice, threshing and cleaning grain while walking in the field. This machine helps farmers where, time and energy to harvest more efficiently and does not require a large amount of labor like traditional (manual) harvesting. This study aimed to calculate and determine the working capacity of the mini combine harvester machine and calculated the work efficiency of the mini combine harvester machine. The method used in this research was experimental using a mini combine harvester type Yanmar model YH150 with Ciherang 32 rice varieties ready to harvest. The results of this study indicated that the effective field capacity is 0.125 ha/hour or 8.028 hour/ha, while the theoretical field capacity was 0.234 ha/hour so that the field efficiency is 53.23%. Keywords: field efficiency, field capacity, rice, mini combine harvester